Staged reduction of neglected transscaphoid perilunate fracture dislocation: A report of 16 cases - Garg, Bhavuk (BioMed Central, 2012)
BACKGROUND: Transscaphoid perilunate fracture dislocation is a rare injury and can be easily missed at the initial treatment. Once ignored, late reduction is not possible and needs extensive dissection. An alternative treatment such as proximal row carpectomy may be required for neglected injuries, but surgical outcome is not as good as that of an early reduction. We aim to present an alternative technique of staged reduction and fixation in patients of neglected transscaphoid perilunate dislocations and study its outcome. MATERIAL & METHODS: 16 cases (14 males & 2 females) with neglected transscaphoid perilunate fracture dislocation (> 3 month old) were treated with staged reduction. Mean duration between injury and surgery was 4.5 months. In first stage an external fixator was applied across the wrist and distraction was done at 1 mm/day. Second surgery was done through dorsal approach and we were able to reduce all the fractures & dislocations. Herbert screws and K wires were used for fixation. RESULTS: The mean duration between two surgeries was 2.4 weeks (range 2–4 weeks). 9 cases had excellent results, 5 had good result. Two patients developed reflex sympathetic dystrophy and had fair results. CONCLUSION: Staged reduction should be considered for neglected transscaphoid perilunate dislocations. If properly executed, a good functional pain free range of motion is the usual outcome.